202k views
2 votes
X^2+6x≤-5 with an explanation pls

User Tesdal
by
4.4k points

1 Answer

2 votes

Answer:

−5≤x≤−1

Step-by-step explanation:hope that helps :)))

x2+6x=−5

x2+6x−(−5)=−5−(−5)(Subtract -5 from both sides)

x2+6x+5=0

(x+1)(x+5)=0(Factor left side of the equation)

x+1=0 or x+5=0(Set factors equal to 0)

x=−1 or x=−5

Check intervals in between critical points. (Test values in the intervals to see if they work.)

x≤−5(Doesn't work in original inequality)

−5≤x≤−1(Works in original inequality)

x≥−1(Doesn't work in original inequality)

Answer:

−5≤x≤−1

User LeZuse
by
4.5k points